RECONFIGURATION OF THE AIRCRAFT INTEGRATED CONTROL SYSTEM REGARDING CONTROL CONSTRAINTS UNDER ACTUATOR FAILURES - A. M. Kulchak; V. V. Kosyanchuk; E. Yu. Zybin (Научный вестник МГТУ ГА, 2018)
The aircraft integrated control system reconfiguration laws under failures of actuators, calculated disregarding physical constraints on control surfaces saturation, can lead to a complete loss of aircraft controllability and stability. Despite the large number of scientific publications in this field, practical systematic results have been obtained only for SISO (single input – single output) systems. Problems of the convergence of iterative algorithms restricting the set of admissible solutions and the conservatism of the reconfiguration laws designed using weight matrices do not allow solving this problem in general. For complex MIMO (multi input – multi output) systems there is still no widely accepted universal approach. In this work, control surfaces constraints are regarded in terms of the power of reconfiguration control. It is shown that by slight modification of pseudoinverse (optimal) solution it is possible to obtain approximate pseudoinverse (suboptimal) solutions with priory known minimum power (compensation matrix norm) and error (residual matrix norm) of the reconfiguration for a given degree of approximation. This allows for a multistep consistent reduction in power and increasing in error of reconfiguration, until an acceptable solution is obtained. By providing the greater reconfiguration error at each step we have additional freedom in reducing the reconfiguration power. This leads to a decrease in the amplitude of the deviations of the control surfaces, to which the signals from the failed control channels are redistributed. The simulation example of the aircraft integrated control system reconfiguration under the stabilizer’s actuator failure is presented. It is shown that the pseudoinverse reconfiguration problem solution leads to the significant ailerons’ constraints violation and the loss of aircraft controllability. Regarding control constraints solution reduces several times the deviation of the control surfaces and provides an effective problem solution in the permissible power and error reconfiguration range.